Double Exile: Jean Rhys's Wide Sargasso Sea - Instructor Nibras Jawad Kadhim (College of Education for Women, 2019)
The problems of cultural displacement and a shaky sense of one's own identity have been the main concern of the twentieth century Caribbean writer, Jean Rhys. As a white Creole writer living in England, Rhys attempts to capture the ambivalence of what it means to be caught between two cultures and never able to identify fully with any one .Born to a Welsh father and a Creole(white West Indian) mother on the island of Dominica in the West Indies, Jean Rhys was white but not English, West Indian but not black. Her sense of belonging to the West Indies was necessarily charged with awareness of being part of another culture. Thus, the ambiguity of being an insider/outsider in both the metropolis, England, and the colony, West Indies, shaped Rhys' world, resulting in her sense of exile and marginality The purpose of the research is to examine how Rhys gives the same sense of exile and marginality to Antoinette Cosway, the heroine of her 1966 novel Wide Sargasso Sea, through whom she reflects the unique experience of dislocation of the white Creole woman.